Assessment of the Philippine Statistical Development Program 2005-2010 : Annexes - World Bank (World Bank, 2012)
The objective of this assessment of the Philippine Statistical Development Plan (PSDP) is to provide recommendations on how to improve the preparation, implementation, coordination, monitoring, and evaluation of the next PSDP during 2011-16. The report also gives two approaches to getting better treatment for the Philippine Statistical System (PSS) from the Department of Budget and Management (DBM), which supervises personnel levels under Executive Order (EO) 366. One is to petition for the earliest possible approval of the rationalization plans submitted by the Major Statistical Agencies (MSAs), inasmuch as the effects of EO 366 are much more benign after than before the approval of a rationalization plan. The other is to lobby with the National Economic and Development Authority (NEDA) for a declaration that statistics are a priority need, so that statistical development begins to be seen as a tool for improved governance and not as a regrettable burden on the budget. In addition, the report examines to what extent and how donor agencies could help with the financing of the next PSDP. Finally, with regard to the design of the next PSDP, the report recommends a much briefer document of about 100 pages than the most recent one with 700 pages. This can be achieved in part by relying more explicitly on the multi-year plans of the MSAs, so that the PSDP can focus on strategic issues, key priorities and budget requirements, cross-sectoral issues, and the development of statistical activities outside the MSAs.